2009
DOI: 10.1021/bc8002259
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor Targeted Bimodal Liposomes for Tumor Magnetic Resonance Imaging

Abstract: Folate-targeted bimodal paramagnetic and fluorescent liposomes were developed and showed enhanced accumulation in a folate receptor expressing tumor model. These bimodal liposomes were composed of both a paramagnetic and a fluorescent lipid, and utilized a PEG-lipid amphiphile for prolonged in vivo circulation. The particles were formulated to ensure a size distribution of approximately 100 nm with a low polydispersity index. IGROV-1 cells were used to induce tumors in nude Balb/c mice, and the folate-targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
99
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 29 publications
(39 reference statements)
2
99
1
Order By: Relevance
“…11 Lipid-based nanoparticles, such as liposomes, micelles, and microemulsions, have been evaluated as carriers of MRI contrast and fluorescent agents for noninvasive imaging. 9,[12][13][14][15][16][17][18][19][20] There are several recent reviews on lipid-based paramagnetic nanoparticles 21,22 and on paramagnetic and fluorescent nanoparticles. 3,10,23,24 Kostarelos and Miller described a modular design for targeted paramagnetic liposomes carrying nucleic acids, termed Gd-ABCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Lipid-based nanoparticles, such as liposomes, micelles, and microemulsions, have been evaluated as carriers of MRI contrast and fluorescent agents for noninvasive imaging. 9,[12][13][14][15][16][17][18][19][20] There are several recent reviews on lipid-based paramagnetic nanoparticles 21,22 and on paramagnetic and fluorescent nanoparticles. 3,10,23,24 Kostarelos and Miller described a modular design for targeted paramagnetic liposomes carrying nucleic acids, termed Gd-ABCD.…”
Section: Introductionmentioning
confidence: 99%
“…27 Kamaly et al showed that FR-targeted fluorescent paramagnetic bimodal liposomes have increased accumulation in a FR + murine tumor model. 13 In this study, the authors report the synthesis and evaluation of FR-targeting bimodal liposomes for MRI and fluorescent imaging based on the previously reported Gd-ABCD design. 25 Gd-DTPA-BSA was incorporated into the bilayer of the liposomes as a paramagnetic agent, whereas calcein, a fluorescent dye, was encapsulated in the aqueous core of liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…When introducing macromolecular carriers, signal enhancement to MRI is improved by shortening the T 1 relaxation time of water protons. 2,[23][24][25] Liposomes are by now one of the most successful nanomedicines, which have been applied to deliver a wide variety of chemical molecules, genes, CAs, and even nanoparticles. 26 Compared with other delivery systems (such as nanoparticles, micelles, and carbon nanotubes), liposomes show superior biocompatibility, biodegradability, relatively low toxicity, and improved control over size and surface functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that by anchoring ligands in liposome bilayers, the affinity and specificity of liposomal systems to specific targets could be enhanced. 24,25,29 Among the target-specific ligands, aptamers have appeared as promising candidates. 3,4,30 Therefore, GBI-10-targeted gadolinium-loaded liposomes (GTLs) were designed and prepared as a MRI CA for the diagnosis of tumor for the first time in this original study.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] Ligand-decorated silica particles have been widely used as analytical and biosensing tools. [31][32][33][34][35][36][37][38][39][40] Timely multi-functional MR imaging contrast-enhancing nanoparticles have been studied in biomedical applications. [41][42][43][44][45][46][47][48][49][50][51][52] With the above in mind, we designed silica nanoparticles to have a dual imaging mode, ie, (MR) imaging and fluorescent optical imaging.…”
Section: Introductionmentioning
confidence: 99%